A Bibliometric Analysis on Financial Inclusion and Financial Literacy – Analyzing the Current Research Trends - Mary Khongwir, Careen; J.C., Sharmiladevi (Indian Journal of Finance, 2023)
Purpose : Bibliometric analysis acts as a road map in research and helps understand the existing body of knowledge. We conducted a bibliometric analysis in the field of financial inclusion (FI) and financial literacy (FL). Design/Methodology/Approach : We used Biblioshiny through R studio on 2,836 documents extracted from WOS and Scopus databases from 1984 to 2022. Findings : We identified prominent authors, highly cited publications, significant themes and keywords, and co-citation networks. Originality/Value : This study used Scopus and Web of Science (WOS) data to conduct the bibliometric analysis. Practical Implications : The research results will be significant to scholars, researchers, and policymakers in FI and FL, as the study showed the roadmap and pathways to scientifically understanding current and future research trends.